Tau propagation is dependent on the genetic background in multiple mouse strains: Molecular and cell biology/tau. (7th December 2020) - Dujardin, Simon; De Los Santos, Mark; Fernandes, Analiese R.; Bannon, Riley N.; Kamath, Tarun V.; Commins, Caitlin; Hyman, Bradley T.
Abstract: Background: The hyperphosphorylation and deposition of tau proteins in insoluble aggregates inside neurons are a hallmark of around 20 pathologies called tauopathies including the well‐known Alzheimer's disease (AD). In AD and other tauopathies, histopathological studies have shown that tau lesions appear progressively and hierarchically in the brain along anatomical connections. The mechanisms underlying such evolution had remained unexplained for many years, but recent evidence support the idea that the evolution across brain areas is the result of the active propagation of tau aggregation within the brain. We and others previously demonstrated in in vitro and in vivo models that tau assemblies are transferred from cell‐to‐cell and, by being taken up by a second cell, seed the aggregation of endogenous tau leading to the propagation of tau lesions in the brain. We hypothesized here that the genetic background of mice influences the propagation of tau across neural networks. Methods: We used a model of tau propagation that we previously described consisting in the injection of adeno‐associated viral vectors (AAV) encoding the eGFP‐2A‐Tau construct into the entorhinal cortex of mice. The 2A peptide is a self‐cleaving peptide resulting in the equimolar independent expression of the eGFP and human tau. Using this model, we can therefore discriminate the neurons expressing the AAVs (GFP and tau positive) from the tau propagation recipient neurons (tau positive only). We injected mice from multiple strains (n = 5 males and 5 females per strain), with diverse genetic backgrounds, with this construct and subsequently quantified the number of neurons positive for tau propagation in each condition. Results: In a blinded analysis we found that the propagation of tau in vivo is highly dependent of the genetic background with strains (such as C57BL/6) that are mostly resilient to tau propagation when other (such as CD‐1 or A/J) show a high degree of tau propagation. Conclusion: these results provide an important insight to the idea that tau propagates from neuron‐to‐neuron in the human pathology. This could explain part of the human clinical heterogeneity and must be investigated further to understand the genetic factors responsible for such drastic differences.